HUBUNGAN KUALITAS TIDUR DENGAN OBESITAS MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2014 - Eka Bebasari; Yanti Ernalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTSleep and rest is primary needs for everyone to make body have a normal function. Decreasing of sleep duration in someone will make some side effect for body and mind. Some study suggest that the shortening of time sleeping in a person can lead obesity which one can caused many other diseases that related with lifestyle such as hypertension and diabetes melitus. This research use analytic method with cross sectional approach to knowing the relationship between sleep quality and obesity in 2014 class student of Medical Faculty University of Riau. Total sample in this study was 137 students. This study was performed to assess the quality of sleep and obesity in respondents. Sleep quality assessment is done by filling out the quistionnaire Pittsburgh Sleep Quality Index (PSQI) and the assessment of obesity is done by Body Mass Index (BMI) by measuring height and weight of respondents using height and weight scales. Research results obtained by sex that there’s 84,7% female respondents and 15,3% male respondents. Results of nutritional state in respondents based on BMI that there’s 59,9% non obesity while 40,1% obesity. Result of sleep quality showed that 68,6% were classified in poor category and 31,4% in good category. Chi square test results that there’s no relationship between quality of sleep with obesity in 2014 Class Students of Medical Faculty University of Riau.Key words : Sleep quality, obesity